International Standards and European Practice in the Field of Anti-Discrimination - Dats , Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The author provides a comprehensive overview of key international instruments such as the UN Convention on the Elimination of All Forms of Racial Discrimination (1965), the UN Convention on the Elimination of All Forms of Discrimination against Women (1979), the Discrimination (Employment and Occupation) Convention (1958), and the Convention on the Elimination of Discrimination in Education (1960). Particular attention is paid to the consideration of direct and indirect forms of discrimination, as well as to the peculiarities of proving these forms of discrimination based on the case law of the European Court of Human Rights.The author points out the importance of European practice, in particular, the ECHR judgments in cases involving violations of anti-discrimination norms. In particular, the author examines the cases of «Mustakim v. Belgium» and «D.H. and Others v. the Czech Republic», which illustrate the peculiarities of consideration of direct and indirect discrimination. The author examines the impact of the European Union's anti-discrimination legislation, in particular Council Directive 2000/43/EC, which establishes the principle of equal treatment regardless of racial or ethnic origin.The author analyses the problematic aspects of Ukraine’s national anti-discrimination legislation, drawing attention to the fact that the current legal framework of Ukraine needs to be improved, as it does not fully comply with international standards and the case law of the ECHR. One of the key elements of the article is the analysis of the evidence base in discrimination cases. It is noted that proving indirect discrimination is more difficult than direct discrimination, as it is often necessary to use statistical data to prove that a certain group of people is exposed to disproportionate negative consequences. The author emphasises the importance of applying the «beyond reasonable doubt» standard of proof used by the European Court of Human Rights in discrimination-related cases, in particular in «hate crime cases». The author emphasises the need to adapt Ukrainian legal acts to European standards, in particular in terms of standards of proof in discrimination cases.